COLONIAL RULE AND MUSLIM WOMEN: Raising Consciousness of the Situation, Regarding their Islamic Legal Status - Maqsood, Dr Naila (Journal of Arts & Social Sciences, 2022)
Relevant to any attempt for amelioration of woman’s conditions was the history of Muslim people in general and that of Muslims in the Indo-Pak Subcontinent in particular. This paper highlights Muslim women’s struggle for their rights movements in British India. Their continuous struggle altered educational and political institutions, allowing them to emerge from seclusion and participate more actively in the nation's public life.It is said that when women in the developed countries were agitating against their own male regarding their rights, a similar struggle had begun in the subcontinent where men started encouraging participation of women in education and politics, appreciated, and sometimes patronized it. The imperialists in India reversed the economic and social milieu. By strengthening system, British fortified the position of the feudal and tribal lords which not only contributed towards solidifying the struggle for Muslim Women’s Rights in the British India but also resulted in lowering the status of women. The British, on the other hand, did not believe it was necessary to extend their politics into all aspects of life. As a result, local laws continued to apply in family and personal matters like as marriage, guardianship, and inheritance, and the status quo between men and women was maintained.  After a prolonged protests and struggle for women’s rights, the central legislature undertook legislation on issues relating to Muslim women such as child marriage, property rights, widow remarriage, divorce, etc. Muslim women had to resisted on the laws imposed by imperialists as most of it were the violation of their fundamental rights, and that they were mostly successful i.e., law of inheritance 1937. The paper shows that women's struggles for educational and political freedom had a significant impact in the British India Particularly in 1940s during Pakistan Movement. Everyone is aware of the social changes/developments that occurred at that time. However, few people acknowledge that women had a key role in bringing about these developments. It is hardly an exaggeration to say that women have achieved tremendous progress and have paved the way for more reforms in late nineteenth and early twentieth centuries.